Management, Supervision, and Health Care: A Field Experiment - Felipe A. Dunsch; David K. Evans; Ezinne Eze-Ajoku; Mario Macis (Institute of Labor Economics (IZA), 2017)
If health service delivery is poorly managed, then increases in inputs or ability may not translate into gains in quality. However, little is known about how to increase managerial capital to generate persistent improvements in quality. We present results from a randomized field experiment in 80 primary health care centers (PHCs) in Nigeria to evaluate the effects of a health care management consulting intervention. One set of PHCs received a detailed improvement plan and nine months of implementation support (full intervention), another set received only a general training session, an overall assessment and a report with improvement advice (light intervention), and a third set of facilities served as a control group. In the short term, the full intervention had large and significant effects on the adoption of several practices under the direct control of the PHC staff, as well as some intermediate outcomes. Virtually no effects remained one year after the intervention concluded. The light intervention showed no consistent effects at either point. We conclude that sustained supervision is crucial for achieving persistent improvements in contexts where the lack of external competition fails to create incentives for the adoption of effective managerial practices.
Keywords: I15; M10; O15; 330; management; health care; supervision; economic development